(3LhGgQ GdaJGhjs - (3GdcQeGfj, TeS GdOjf, eMeO Hf jhSa Hf Ydj Hf SYjO, J (B786(3g`s
(3ChdgG (B:s
(3ChMjJ HPdc abGdJ Cfj GeQCI VFjdI Cj fMjaI hCfj CcQg Cf jbY CHUGQ GdefGabjf Ydj ShdOjs
(3BNQgG (B:s
(3ef GdSdWGf jJfGhd GdeGd ajUjQ GdeTJQc ajUjQ cGdfGQ hbY aj GdQMd hGQb TjG Cfg jchf ef Gdcds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 204s
(3GdCYdGe (B3 / 409s
(3cTa GdXfhf (B1 / 615s
(3GdLhGgQ GdeVjI (B2 / 81s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs